Integrating Biofortification Indicators into CAADP Biennial Reviews - Maru, Joyce; Kwikiriza, Norman; Saika, Sheewa (CGIAR System Organization, 2023)
Throughout the past three Biennial review (BR) cycles (2017, 2019, 2021) Kenya’s active engagement as the Comprehensive Africa Agriculture Development Program (CAADP) and commitments to the CAADP Malabo framework has been evident. However, the integration of biofortification indicators has not been an integral part of the BR cycles. Since March 2023, The International Potato Center( CIP ) has closely collaborated with the government of Kenya through the Ministry of Agriculture and Livestock in conducting a series of capacity-sharing workshops and knowledge-sharing to ensure that biofortification is well integrated into the BR review.